A scoping review of the role of the arts in enhancing data literacy - Helen Phelan; Fran Garry; Ailish Hannigan (PLoS ONE, 2025)
With the growing use of personal and public data in everyday life, data literacy is increasing in importance. There is a significant body of research indicating the role of artistic practice in the regulation of our response to information and experience, particularly as these relate to experiences of trust and social bonding. However, there is a gap in the literature concerning a review of current publications investigating the use of artistic practices to enhance data literacy. The aim of this study was to conduct a scoping review to identify and map the extent of evidence available on this topic. Specifically, the review aims to contribute to a better understanding of which artistic practices and art forms were being used, the profile of population groups and settings, and the rationale provided for using the arts. Our review utilized Arksey and O’Malley’s methodological framework. The review includes an updated search, conducted in April 2025, to provide a comprehensive overview of recent studies. Following abstract and full text screening, a total of 51 publications were deemed eligible for review. The findings indicate the use of a broad spectrum of artistic practices, with visual arts and storytelling being the most prevalent. Most of the research to date has been conducted within educational settings. The arts were identified as key tools in enhancing accessibility, engagement and critical thinking when engaging with data. Limits in the value of harnessing artistic practices for data literacy were noted, including the sometimes competing demands of artistic freedom and scientific exactitude. Further research is needed to more fully understand the importance of cultural context in how the arts are deployed in the dynamic and rapidly changing world of data.